2000
DOI: 10.1016/s0925-4439(00)00052-1
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of chronically administered all-trans-retinoyl-β-glucuronide in mice

Abstract: After the subcutaneous injection of retinoyl beta-glucuronide (RAG), both RAG and retinoic acid (RA), formed by the hydrolysis of RAG in vivo, achieved peak plasma concentrations within 1-2 h. Thereafter, RA was rapidly cleared from the plasma whereas RAG was eliminated much more slowly. No significant changes were noted in the peak (2 h) plasma levels of RAG for treatment periods up to 56 days (one injection of RAG/day), in the clearance rate of RAG from plasma, or in plasma retinol concentrations. Similarly,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2001
2001
2004
2004

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 25 publications
3
11
0
Order By: Relevance
“…In contrast, while maximal increases in the formation of neurites occurred at PA concentrations between 5 and 10 mM, 4-CPA was found to be about threefold more potent with maximal neurite-inducing activity occurring at about 3 mM. As previously reported (Sidell et al, 2000), RAG also induced neurite sprouting from LA-N-5 cells, with maximal effects seen at RAG concentrations in the 5 -10 mM range after extended periods (46 days). These morphologic changes are similar to those extensively reported after RA treatment of LA-N-5 cells (Sidell et al, 1983;Robson and Sidell, 1985), with the exception that maximal neurite outgrowth is seen with RA at somewhat lower concentrations (41 mM).…”
Section: Morphologic Differentiationsupporting
confidence: 62%
See 4 more Smart Citations
“…In contrast, while maximal increases in the formation of neurites occurred at PA concentrations between 5 and 10 mM, 4-CPA was found to be about threefold more potent with maximal neurite-inducing activity occurring at about 3 mM. As previously reported (Sidell et al, 2000), RAG also induced neurite sprouting from LA-N-5 cells, with maximal effects seen at RAG concentrations in the 5 -10 mM range after extended periods (46 days). These morphologic changes are similar to those extensively reported after RA treatment of LA-N-5 cells (Sidell et al, 1983;Robson and Sidell, 1985), with the exception that maximal neurite outgrowth is seen with RA at somewhat lower concentrations (41 mM).…”
Section: Morphologic Differentiationsupporting
confidence: 62%
“…Previous studies have demonstrated the antiproliferative effects of RAG on LA-N-5 cells and indicated that this retinoid was 5 -10-fold less potent than RA on a concentration-dependent basis (Sidell et al, 2000). Figure 2 shows the dose-dependent effects of 4-CPA on the growth of LA-N-5 cells as assessed by SRB protein staining.…”
Section: Proliferationmentioning
confidence: 89%
See 3 more Smart Citations